2016
DOI: 10.1093/europace/euw026
|View full text |Cite
|
Sign up to set email alerts
|

Midterm clinical outcomes of concomitant thoracoscopic epicardial and transcatheter endocardial ablation for persistent and long-standing persistent atrial fibrillation: a single-centre experience

Abstract: The hybrid procedure yields promising results in the setting of both persistent and long-standing persistent AF after midterm follow-up, at the expense of a non-negligible rate of adverse events. Our findings need to be confirmed by further larger and prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 17 publications
3
44
1
3
Order By: Relevance
“…Fortunately, we could reduce the prevalence of phrenic nerve palsy dramatically using bipolar-type electrocautery (Harmonic scalpel). In the report by de Asmundis et al, postoperative complications after epicardial surgery were reported to occur in up to 17% of total cases, but the majority of complications was minor and shortterm and recovered without any sequela (17). The only complication, which is still a difficulty, is acute pericarditis.…”
Section: Safety Of Thoracoscopic Epicardial Ablationmentioning
confidence: 97%
“…Fortunately, we could reduce the prevalence of phrenic nerve palsy dramatically using bipolar-type electrocautery (Harmonic scalpel). In the report by de Asmundis et al, postoperative complications after epicardial surgery were reported to occur in up to 17% of total cases, but the majority of complications was minor and shortterm and recovered without any sequela (17). The only complication, which is still a difficulty, is acute pericarditis.…”
Section: Safety Of Thoracoscopic Epicardial Ablationmentioning
confidence: 97%
“…The reported efficacy in the published study by de Asmundis was that 67.2% of patients were in sinus rhythm and no longer needed antiarrhythmic drugs (AAD) 2 years after ablation (1). Keeping in mind that all patients had persistent and long-standing persistent AF, the efficacy was very good.…”
Section: Thoracoscopic Ablation-reported Efficacymentioning
confidence: 98%
“…58 In a collaboration between cardiothoracic surgeons and electrophysiologists, percutaneous endocardial catheter mapping and ablation were first added to epicardial thorascopic ablation with the hope of increasing the success rates by combining potential advantages of each separate procedure. 59 This hybrid AF procedure allowed for fast epicardial placement of extensive linear lesions with the endovascular validation of complete bidirectional conduction block. The convergent ablation procedure is different from previous hybrid ablations in that it employs a novel device to perform epicardial ablation via a transdiaphragmatic approach.…”
Section: Atrial Fibrillationmentioning
confidence: 99%